Nanoelectromechanical switch with low voltage drive - Jang, J; Cha, S; Choi, Y; Butler, T; Kang, D; Hasko, D; Jung, J; Jin, Y; Kim, J; Amaratunga, G (2008)
The triode structure vertical carbon nanotube based nanoelectromechanical switch shows excellent low voltage drive (∼4.5 V), owing to its vertical gate and the narrow gap between structural elements. The insulator deposition and the selective etching process steps simplify fabrication through self-alignment. The thickness of the insulator determines the width of the gap and the etching process, used to produce the vertical gate, removes the need for a complicated lithography step. The low drive voltage increases device stability and reliability and allows the device to be deployed in a wide range of applications. © 2008 American Institute of Physics.